PERANCANGAN PROGRAM APLIKASI SISTEM PAKAR UNTUK PENGENDALIAN POLA MAKAN BAGI PENDERITA PENYAKIT DIABETES MELLITUS - Maisyaroh Maisyaroh; Lutfi Adhaeri (LPPM Universitas Bina Sarana Informatika, 2015)
Diabetes Mellitus (DM) is a metabolic disorder that is most common, with an estimated prevalence of worldwide between 1%-5% (Susztak et al., 2006). The number of sufferers diabetes was increase at the global. Unfortunately not many of the practitioners of computer or informatics was concerned with the complexity of diabetes disease, especially for help the expert or professional preparing nutrition diet for diabetic patients to make balanced nutritional needs and help his healing disease diabetic. Expert system are computer based system that use knowledge, in facts and research to solve the problem which usually worked by expert or professional in particular field. Expert system are really solving the problem in this moment where the information of technology was increase. This expert system program produce the output information calories daily needs and a list menu for the sufferers. Daily calories needs is obtained from the body mass index was calculated from weighte and height of the patients also the nutrition of patients.